2015
DOI: 10.1007/s10488-014-0619-4
|View full text |Cite
|
Sign up to set email alerts
|

Emergency Mental Health Services for Children After the Terrorist Attacks of September 11, 2001

Abstract: Much literature documents elevated psychiatric symptoms among adults after the terrorist attacks of September 11, 2001 (9/11). We, however, know of no research in children that examines emergency mental health services following 9/11. We test whether children's emergency services for crisis mental health care rose above expected values in September 2001. We applied time-series methods to California Medicaid claims (1999 to 2002; N= 127,200 visits). Findings in California indicate an 8.7 percent increase of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…Although researchers may find it difficult to gain access to children soon after a terror event, certain evidence suggests that children do experience immediate effects on their mental health. Recently, Bruckner et al (2016) analyzed emergency mental health services for Californian children on Medicaid from June 1999 to June 2003. They found a statistically significant spike in emergency mental health services for children in the month after 9/11 (Bruckner et al, 2016).…”
Section: Children’s Reactions To Disastermentioning
confidence: 99%
See 1 more Smart Citation
“…Although researchers may find it difficult to gain access to children soon after a terror event, certain evidence suggests that children do experience immediate effects on their mental health. Recently, Bruckner et al (2016) analyzed emergency mental health services for Californian children on Medicaid from June 1999 to June 2003. They found a statistically significant spike in emergency mental health services for children in the month after 9/11 (Bruckner et al, 2016).…”
Section: Children’s Reactions To Disastermentioning
confidence: 99%
“…Recently, Bruckner et al (2016) analyzed emergency mental health services for Californian children on Medicaid from June 1999 to June 2003. They found a statistically significant spike in emergency mental health services for children in the month after 9/11 (Bruckner et al, 2016).…”
Section: Children’s Reactions To Disastermentioning
confidence: 99%
“…Studying children—nonparticipants in the labor force who are affected by job loss and economic stress affecting their caretakers—Bruckner, Kim, and Snowden (2014) demonstrated that a contracting economy precipitated more African American children’s than White children’s use of psychiatric emergency services. Notably, a noneconomic shock, the very distressing September 11, 2001, attacks on the World Trade Center, was associated with lesser use of psychiatric emergency services among African American children than White children (Bruckner et al, 2014). Conceivably, African Americans’ lesser response to this noneconomic crisis arose from their deeper and longer lasting poverty and its concomitant restriction of their focus to economic vulnerabilities and to coping with personal economic challenges (Mullainathan & Shafir, 2013).…”
Section: Enlarging or Shrinking The Safety Net In Response To Economi...mentioning
confidence: 99%
“…The studies that have focused on children have largely examined the immediate effects of 9/11, the Great Recession, or Hurricane Sandy. For example, studies have found increased risk of mental disorders and increased prevalence of psychological symptoms, including anxiety and posttraumatic stress response, among children after 9/11 (Barnes, Treiber, & Ludwig, ; Bruckner et al., ; Calderoni, Alderman, Silver, & Bauman, ; Fairbrother, Stuber, Galea, Fleischman, & Pfefferbaum, ; Hoven et al., ). Studies on the Great Recession and Hurricane Sandy have also suggested associations between these events and increased short‐term mental health difficulties among children and adolescents, but such studies have not been population‐based (Fink & Galea, ; Kalil, ; Kopala‐Sibley et al., ).…”
mentioning
confidence: 99%